The effect of marathon run on urinary excretion of magnesium - Ratkowski, W.; Kaczor, J. J.; Mroczynski, Z.; Popinigis, J. (Medycyna sportowa, 2001)
The problem of post exercise magnesuria was investigated in 3 top Polish marathon runner. The urine was collected first 24 hr before the marathon, and then 5,6 and 10 hr after the run respectively. In all 3 runners significant reduction in the rate of magnesium excursion was noted. The collection of urine in 2 runners was continued up to 21 - 25 hr after the run. And during this period the rates of urinary magnesium excretion were respectively 166% and 312% above resting rates.